THE SOCIO-CULTURAL VALUE OF TECHNOLOGY IN THE CONTEXT OF TEMPORAL ACCELERATION AND GAMIFICATION OF REALITY - Natalia N. Pluzhnikova; Anastasiya V. Gribova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. In the context of digitalization of reality, the analysis of the essence of technology, which is associated with the transformation of modern socio-cultural processes, acquires special scientific significance. Technology is no longer considered exclusively as a technological phenomenon. Acceleration of socio-cultural dynamics processes leads to an expansion of the understanding of technology by including the sphere of technology in all spheres of modern human life. This process is most clearly demonstrated by the example of the development of the cyber-gaming industry, which allows us to substantiate the essence of the value approach to the analysis of technology.